2019
DOI: 10.1177/0333102419896370
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-rapid brain uptake of subcutaneous sumatriptan in the rat: Implication for cluster headache treatment

Abstract: Background In spite of the substantial therapeutic efficacy of triptans, their site of action is still debated. Subcutaneous sumatriptan is the most efficacious symptomatic treatment for cluster headache (CH) patients, showing therapeutic onset within a few minutes after injection even in migraine patients. However, whether subcutaneous sumatriptan is able to reach the CNS within this short time frame is currently unknown. Methods Here, by means of liquid chromatography/mass spectrometry, we investigated perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Data suggests that overall, the triptans seem to remain largely restricted to peripheral nervous system (PNS) sites of action [6]. However, recent evidence in rats suggests that subcutaneous sumatriptan can accumulate rapidly in the central nervous system (CNS) [7,8]. The development and clinical efficacy of non-vasoconstriction drugs for the treatment of migraine led to the conclusion and current predominate theory that vasoconstriction is not the triptan's therapeutic mechanism of action.…”
Section: Introductionmentioning
confidence: 99%
“…Data suggests that overall, the triptans seem to remain largely restricted to peripheral nervous system (PNS) sites of action [6]. However, recent evidence in rats suggests that subcutaneous sumatriptan can accumulate rapidly in the central nervous system (CNS) [7,8]. The development and clinical efficacy of non-vasoconstriction drugs for the treatment of migraine led to the conclusion and current predominate theory that vasoconstriction is not the triptan's therapeutic mechanism of action.…”
Section: Introductionmentioning
confidence: 99%
“…A recent animal study showed that the highest sumatriptan concentration in the CNS was reached in the hypothalamus after 1 and 5 min of a subcutaneous injection of the drug (10). It is noteworthy that the hypothalamic concentration of the drug was higher compared to the trigeminal ganglion and the meninges (10), both peripheral sites where sumatriptan is commonly thought to exert its action in CH. The administration of 6 mg subcutaneous sumatriptan in humans was associated with a decrease in 5-HT 1B receptor binding in the brain, particularly in pain-modulating regions (11).…”
Section: Discussionmentioning
confidence: 99%
“…In an animal model of TAC, sumatriptan reduced the activity in the trigeminocervical complex (TCC) after parasympathetic activation more than the CGRP-receptor antagonist olcegepant (9). A recent animal study showed that the highest sumatriptan concentration in the CNS was reached in the hypothalamus after 1 and 5 min of a subcutaneous injection of the drug (10). It is noteworthy that the hypothalamic concentration of the drug was higher compared to the trigeminal ganglion and the meninges (10), both peripheral sites where sumatriptan is commonly thought to exert its action in CH.…”
Section: Discussionmentioning
confidence: 99%
“…In the late 1980s, some serotonin agonists, known as triptans, were developed for the treatment of migraine. Intranasal sumatriptan (SMT) is the gold standard treatment for severe migraines (Muzzi et al, 2020). However, SMT is a hydrophilic molecule, which limits its permeation through the nasal mucosa and makes it difficult to cross the blood-brain barrier (BBB), despite SMT action on the central nervous system (Pascual and Muñoz, 2005;Tfelt-Hansen, 2010).…”
Section: Introductionmentioning
confidence: 99%